Identifikasi Kesadaran Siswa SDN 3 Jugo Terhadap Konservasi Kupu-Kupu - Sulistiyowati, Tutut Indah; Zunaidah, Farida Nurlaila (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
This community service activity was done in January 2020. The student didn’t understand about butterfly diversity. The purpose of this activity is to educate the student about butterflies diversity in ​​Irenggolo. Qualitative approach method is used in this activity. Data collection techniques using observation, documentation, interviews, and questionnaires. 78% of SDN 3 Jugo students do not understand the diversity of butterflies. After getting an explanation about conservation, students' understanding of conservation is increased from 37% to 72%.